2019
DOI: 10.1093/cvr/cvz322
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase 4 mediates the protective effects of physical activity against obesity-induced vascular dysfunction

Abstract: Aims Physical activity is one of the most potent strategies to prevent endothelial dysfunction. Recent evidence suggests vaso-protective properties of hydrogen peroxide (H2O2) produced by main endothelial NADPH oxidase isoform 4 (Nox4) in the vasculature. Therefore, we hypothesized that Nox4 connects physical activity with vaso-protective effects. Methods and results Analysis of the endothelial function using Mulvany Myograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 64 publications
0
16
0
1
Order By: Relevance
“…Although different NOX4 subcellular localization has been reported, including in the nucleus and endoplasmic reticulum [76,77], NOX4 has been shown to mainly localize in mitochondria, especially in the heart [78][79][80]. Indeed, several beneficial effects of exercise in the vasculature and skeletal muscle, such as increased physical activity, are diminished in NOX4-knockout mice [81]. Furthermore, Hancock et al conclusively demonstrated that Nrf2 activation by AES is mediated by NOX4 and contributes to mitochondrial quality control using cardiomyocyte-specific knockout of NOX4 and Nrf2 (csNrf2 KO) [73].…”
Section: Role Of Mtros and Nrf2 In Mediating The Healthy Effect Of Exmentioning
confidence: 99%
“…Although different NOX4 subcellular localization has been reported, including in the nucleus and endoplasmic reticulum [76,77], NOX4 has been shown to mainly localize in mitochondria, especially in the heart [78][79][80]. Indeed, several beneficial effects of exercise in the vasculature and skeletal muscle, such as increased physical activity, are diminished in NOX4-knockout mice [81]. Furthermore, Hancock et al conclusively demonstrated that Nrf2 activation by AES is mediated by NOX4 and contributes to mitochondrial quality control using cardiomyocyte-specific knockout of NOX4 and Nrf2 (csNrf2 KO) [73].…”
Section: Role Of Mtros and Nrf2 In Mediating The Healthy Effect Of Exmentioning
confidence: 99%
“…Physiologically, Nox4 appears to play a significant role in regulating the metabolic and vascular adaptions needed during exercise [ 151 , 152 ]. Nox4-deficient mice had impaired glucose and fatty acid oxidation in response to acute exercise.…”
Section: Nox4 and Endothelial Functionmentioning
confidence: 99%
“…Furthermore, following a chronic exercise regime, NOX4 -deficient mice had worse exercise capacity (measured by a reduced time to exhaustion) and reduced activity of skeletal muscle citrate synthase and beta-hydroxyacyl-coA dehydrogrenase (important enzymes involved in mitochondrial metabolism) compared to their wild-type litter mates [ 151 ]. Access to an exercise wheel prevented endothelial dysfunction in wild-type, but not Nox4 −/− deficient mice fed a high fat diet [ 152 ]. Exercise of wild type mice resulted in increased H 2 O 2 release in the aorta with increased phosphorylation of Akt and activation of eNOS, whereas both H 2 O 2 release and phosphorylation of Akt were reduced in aortas of Nox4 −/− mice.…”
Section: Nox4 and Endothelial Functionmentioning
confidence: 99%
“… Footnotes. a Exercise has benefits other than weight loss, some of them may be “antioxidant” by upregulating endogenous antioxidant defences [ 82 , 84 , 85 ]. b May depend on how well glucose and lipids have been normalized in the diabetic cohorts studied.…”
Section: A Failure Of Antioxidants Does Not Negate the Importance Of mentioning
confidence: 99%
“… a Exercise has benefits other than weight loss, some of them may be “antioxidant” by upregulating endogenous antioxidant defences [ 82 , 84 , 85 ]. …”
Section: A Failure Of Antioxidants Does Not Negate the Importance Of mentioning
confidence: 99%